A State of Alcohol Hangover Impedes Everyday Prospective Memory - Heffernan, Thomas (Frontiers in Human Neuroscience, 2018)
The aim of the current study was to investigate what impact a state of alcohol hangover has upon everyday prospective memory (memory for future events/intentions). Previous research has shown that the alcohol hangover (AH) has a detrimental effect upon cognitive abilities, including memory and attentional deficits. No published research papers to date have focused upon what impact AH might have upon everyday memory, of which prospective memory is a good example. The current study compared an alcohol hangover group (AHG) with a non-hangover group (NHG) on prospective memory (PM). Since other drug use and mood can affect prospective memory independent of the AH, these covariates were controlled for in the study. Fifty-eight young adults studying at university participated in this between-subjects design study - 25 in the AHG and 33 in the NHG. The Prospective Remembering Video Procedure (PRVP) measured PM. The Acute Hangover Rating Scale confirmed a state of alcohol hangover and a Digital Breath Analyzer Test measured their BAC. The Hospital Anxiety and Depression Scale gauged levels of depression and anxiety and a Recreational Drug Use Questionnaire measured alcohol and other drug use. Anyone who reported having used an illicit substance (e.g., cannabis, ecstasy) or who smoked, were excluded from the study. After controlling for age, alcohol units per week, years spent drinking alcohol, depression and anxiety scores, a 1-way ANCOVA revealed that the AHG (mean =5.16) recalled significantly fewer items on the PRVP than the NHG (mean = 7.51) – F (1,52) = 5.69, p < .05. Since none of the covariates had any significant impact upon the main PRVP scores and in order to increase the power of the test, an ANOVA was run without any of these covariates included, resulting in an increased F value - F (1,56) = 16.6, p < .001. Overall, it appeared that a state of alcohol hangover significantly impaired prospective memory, which was not attributable to age, mood or other drug use. Given the importance of PM to everyday activities, such as remembering to keep appointments or to take an important medication on time, this finding may have far-reaching implications.